COMPARITIVE ANALYSIS OF PROXIMATE COMPOSITION OF HEAD FROM WILD AND FARMED CATLA CATLA - B. Hussain; S. Mahboob; M. Hassan; F. Liaqat; T. Sultana; H. Tariq (Journal of Animal and Plant Sciences, 2011)
The present study was planned to find out the proximate composition of head of wild and farmed Catla catla under three different weight categories because head is mainly disposed. The moisture contents in head from wild and farmed Catla catla were recorded as 63.06 ± 0.46% and 54.91± 0.53%, respectively. Protein contents in head from wild and farmed Catla catla were measured as 14.77 ± 0.37% and 19.92 ± 0.44%, respectively. Lipids contents were recorded as 7.56 ± 0.46% in head of wild and farmed Catla catla respectively. There were 12.26 ± 0.52 % and 12.40 ± 0.31% ash contents in head of wild and farmed Catla catla respectively. The total nitrogen free extract were 2.31 ± 0.05% in wild and 0.74 ± 0.03% in farmed Catla catla. It was concluded that farmed fish contain more lipid and protein contents as compared to that of wild fish. No significant differences were found in case of ash contents. For each parameter seven samples were used and statistical analysis revealed that there are significant differences in case of wild and farmed fish.
Keywords: Wild; farmed; Catla catla; head; composition